Unique mechanical properties of Cu/(NbMoTaW) nanolaminates. (September 2018) - Zhao, Y.F.; Wang, Y.Q.; Wu, K.; Zhang, J.Y.; Liu, G.; Sun, J.
Abstract: Nanostructured face-center-cubic/body-center-cubic Cu/(NbMoTaW) multilayers were prepared with equal layer thickness ( h ) spanning from 5 to 100 nm. The hardness was found to increase with reducing h to ~50 nm, following the Hall–Petch relation. Below this critical thickness, a hardness plateau emerged indicative of an interface barrier strengthening mechanism. The high density of misfit dislocations at interfaces facilitates the yielding of high entropy alloy NbMoTaW layers at stresses far less than the strength of Cu/(NbMoTaW) estimated by rule-of-mixture. Compared with reported multilayers, the present Cu/(NbMoTaW) samples show the size-independent hardness at a larger size-range h  < 50 nm. Graphical abstract: Unlabelled Image